LAW ENFORCEMENT AGAINST ARMED CRIMINAL GROUPS IN CREATING SECURITY AND TRANQUILITY IN PAPUA - Figih Dwi Arganata; Danial Syah; Indra Gunawan Purba (LPPM YPITI, 2026)
Law enforcement against Armed Criminal Groups (KKB) in Papua involves various efforts to crack down on criminals and maintain security and order. Law enforcement in dealing with armed criminal groups in Papua involves a complex approach, combining decisive action by the police and the TNI, as well as persuasive and dialogue approaches, with a focus on the protection of human rights. The government designated the KKB as a terrorist organization, but the handling of the law must also pay attention to human rights aspects and local socio-cultural approaches. Firm and legal actions are in the form of determining terrorist status, joint TNI-Polri operations, criminal law enforcement, investigation and prosecution, persuasive approaches and dialogue, conflict resolution and conducting dialogue. The role of the police against armed criminal groups in creating security and order in Papua has an important role in creating security and order in Papua, especially in dealing with Armed Criminal Groups (KKB).